Improving Student Learning Motivation in Islamic Education Learning by Implementing the Discovery Learning Model at SD Negeri Teupin Peuraho - Aisyah; Yuliya Tursina (Journal of Action Research in Islamic Education, 2025)
This study aims to improve the learning motivation of fourth-grade students of Teupin Peuraho Elementary School towards fasting material through the application of the Discovery Learning learning model. This type of research is Classroom Action Research (CAR) which is carried out in two cycles. The research subjects consisted of 22 fourth-grade students. Data were collected through learning motivation questionnaires, observation sheets, journals, and learning outcome tests. Data analysis was carried out descriptively quantitatively by calculating the average learning motivation score and the percentage of student improvement in each cycle. The results showed an increase in student learning motivation, where the average learning motivation score in the pre-cycle was in the sufficient category, increased to good in Cycle I, and reached the excellent category in Cycle II. This shows that the application of the Discovery Learning model is able to encourage students to be more active, creative, and confident in the learning process, as well as improve their understanding of the fasting material. Thus, exploration-based learning and independent discovery are proven effective in improving student learning motivation.